2014
DOI: 10.1255/ejms.1283
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Pressure Matrix-Assisted Laser Desorption/Ionization Mass Spectrometry of Friction Modifier Additives Analyzed Directly from Base Oil Solutions

Abstract: To develop new products and to apply measures of quality control quick and simple accessibility of additive composition in automo- tive lubrication is important. The aim of this study was to investigate the possibility of analyzing organic friction modifier additives by means of atmospheric pressure matrix-assisted laser desorption/ionization mass spectrometry [AP-MALDI-MS] from lubricant solu- tions without the use of additional separation techniques. Analyses of selected friction modifier ethoxylated tallow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In the reference lubricant mixture, i.e., both FM additives in base oil before tribotesting, all protonated molecular ions of the additives were identified in positive ion mode. High accuracy Orbitrap-MS yielded m / z 282.28 for oleic acid amide FM additive and m / z 302.30, m / z 316.32, m / z 330.34, m / z 346.33, m / z 356.35, m / z 358.37, m / z 372.35, and m / z 400.38 for corresponding structures of the polyethoxylated tallow amine with different lengths of saturated and unsaturated alkyl chains . The identities of the structure of additives were confirmed via CID-fragmentation of the corresponding precursor ions.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…In the reference lubricant mixture, i.e., both FM additives in base oil before tribotesting, all protonated molecular ions of the additives were identified in positive ion mode. High accuracy Orbitrap-MS yielded m / z 282.28 for oleic acid amide FM additive and m / z 302.30, m / z 316.32, m / z 330.34, m / z 346.33, m / z 356.35, m / z 358.37, m / z 372.35, and m / z 400.38 for corresponding structures of the polyethoxylated tallow amine with different lengths of saturated and unsaturated alkyl chains . The identities of the structure of additives were confirmed via CID-fragmentation of the corresponding precursor ions.…”
Section: Resultsmentioning
confidence: 92%
“…Atmospheric pressure-matrix assisted laser desorption/ionization-mass spectrometry (AP-MALDI-MS) was developed around the turn of the century and has been strongly improved over the years by using various types of mass spectrometers , and different types of lasers. In recent years, AP-MALDI has been widely used for analytical purposes in proteomics and the emerging field of lipidomics. ,, Only a little research has been carried out on additives such as cationic surfactants from wastewater, , as well as ethoxylated surfactants and antioxidants from lubricants, but no comprehensive study on organic friction modifiers (FM) utilizing AP-MALDI is known. Only recently, the general possibility to analyze friction modifier additives directly from base oil solutions via AP-MALDI-MS has been introduced . Furthermore, several materials have been used as AP-MALDI targets in previous studies, whereas the gold-covered metal target showed superior desorption/ionization yield. , …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…32,33 Atmospheric pressure matrix-assisted laser desorption/ionization (AP-MALDI) is complimentary to the previously mentioned analytical methods and already a powerful tool to analyse proteomes and lipidomes. 34,35 Moreover, this technique has also been already successfully adopted for characterization of lubricant oils to detect additives such as anti-oxidants 36 and frictions modifiers 37 directly from base oil solutions as well as from tribologically stressed steel surfaces. 38 In addition, previous studies have used different surface materials as AP-MALDI targets, with the gold-coated steel target showing superior desorption/ionization yield.…”
Section: Introductionmentioning
confidence: 99%